Avaliação da potencialidade do tecnécio-99m-DTPA e do tecnécio-99m-fitato de sódio, livres e encapsulados em lipossomas, na identificação de processos inflamatórios - Luciene das Gracas Mota (2011)
The inflammatory and infectious diseases are one of the most common causes of mortality and morbidity. This paper presents the evaluation of the potential of the radiopharmaceuticals 99mTc-DTPA and 99mTc-Sodium Phytate, free and encapsulated into long-circulating and pH-sensitive (SpHL) to identify inflammatory process. Thephysicochemical characterization of freeze-dried SpHL constituted byaPEG2000-DSPE:DOPE:CHEMS (0.5:6.5:3.0 molar ratio, respectively) lyophilized in the presence of glucose as cryoprotectant at cryoprotectant:phospholipid ratio (w/w) 5:1, showed 80% of the vesicles with a diameter smaller than 350 nm, showing good homogeneity(PI=0.29). SpHL (lipid concentration of 20 mM) showed higher encapsulation efficiency, and positive zeta potential. SpHL stored in refrigerator (4°C) did not show significant changes in the mean diameter up to 180 days of storage, showing good stability. The percentage ofencapsulation of the 99mTc-DTPA in SpHL was 10.65% and 4.88% were adsorbed on the surface of the vesicles. The average diameter of SpHL-99mTc-DTPA was 207.4 ± 8.5 nm, showing good homogeneity. The SpHL radiolabeled with 99mTc-Sodium Phytate showedvesicles with mean diameter of 293.1 ± 10.4 nm and the encapsulation percentage of 14.43%. Radiopharmaceuticals 99mTc-DTPA or 99mTc- Sodium Phytate, free and encapsulated into SpHL were administered intravenously in mice-bearing inflammation focus induced by Zimosan suspension at 5% (w/v) Biodistribution studies showed significantuptake of radiolabeled SpHL in the organ of the mononuclear phagocytic system (liver and spleen). The 99mTc-DTPA, free and encapsulated, were able to identify the inflammatory focus by scintigraphic images at 2 hours post-injection. The target/ non-target ratio was greater than 1.5 for all times investigated. The data did not show statistically significantdifference between the free and encapsulated radiopharmaceuticals. The 99mTc-Sodium Phytate, free and encapsulated into SpHL also were effective to identify inflammatory process. The target/non-target ratio for 99mTc-Sodium Phytate free was higher than that obtained with SpHL-99mTc-Sodium Phytate during the entire experiment, reaching a value of 10.24 at 2 hours post-injection. These results suggesting that the 99mTc-Phytate Sodium could be employed as alternative procedure to identify inflamed.regions.